Right of Muslim women in refusing polygamy from Islamic perspective and Islamic law in Malaysia - Mahmud , Mek Wok; Naping, Herna (2015)
The practice of polygamy is severely and frequently criticized especially by the feminist groups. Those people argue that polygamy contributes to discrimination of women, matrimonial disharmony and the worst thing to divorce.Thus, the purpose of this study is to determine whether Muslim women have the right to refuse polygamy. At this juncture, it is significant to have a clear mind that basically a wife cannot stop her husband from marrying other women to the maximum of four.Nonetheless, it is essential for the wife to know whether she has the right to refuse or challenge subsequent marriage or not. This study will adopt a content analysis method whereby the jurists’ opinions, Shari’ah Courts’ decision as well as the Islamic law pertaining to polygamy are referred to.The findings revealed there are some existing factors and situations that wives have the right to refuse or challenge polygamy.